The Teacher-Parent Social Collaboration in Fostering Moral Education of Santri at the Qur’anic Islamic Boarding School in Kisaran - Ikke Nurjanah Sinaga; Zulkipli Lessy (Fakultas Tarbiyah IAIN Fattahul Muluk Papua, 2026)
The lack of effective collaboration between teachers and parents in Islamic boarding schools has become a significant issue in Islamic education today. This leads to a decline in the quality of education for santri, resulting in low motivation, poor academic achievement, and a weakening of moral values and ethics among students. This study aims to investigate the collaboration between teachers and parents in improving the moral development of santri at the Qur’anic Islamic Boarding School in Kisaran, North Sumatra. A qualitative descriptive research method was used, with data collected through interviews, observations, and documentation. Data analysis involved reducing irrelevant data and drawing conclusions based on the collected information. The research findings indicate that the social collaboration between teachers and parents is relatively effective. Teachers and parents regularly meet, communicate the importance of monitoring santri’s activities at both home and the boarding school, and observe their worship practices. There is intense communication between teachers, parents, and santri, creating a strong synergy that helps to strengthen the moral values of the santri. The study also discusses supporting and inhibiting factors for collaboration. Effective collaboration between teachers and parents plays a crucial role in enhancing the quality of education and reinforcing the moral values of santri, which is essential for their future development.